Analisis Pergerakan Penumpang Angkutan Umum Terhadap Aksesibilitas Di Kota Malang - Candra Atma Romadhon, Dicky; Arifianto, Andy Kristafi; M. Sa'dillah (Jurnal Civil Engineering Study, 2025)
Public transportation plays a crucial role in supporting urban mobility. In Malang City, public transportation (angkot) faces various challenges, particularly declining service quality and increasing competition from online transportation. This study aims to identify the characteristics of angkot, analyze passenger movement patterns, and plan efforts to improve accessibility. The study employed a quantitative descriptive approach with multiple linear regression analysis using SPSS. Data were collected from 101 respondents at five main terminals using simple random sampling and incidental sampling techniques. The results showed that there were still 17 active routes with MPU/CARRY vehicles with a capacity of 10–12 passengers without a clear departure schedule. Of the 19 bus stops, most were not functioning properly, while angkot fares were not in accordance with regulations. Regression analysis showed that comfort, safety, and facility conditions simultaneously significantly influenced efficiency and connectivity, with a determination value (R²) approaching 1,000. Comfort and safety factors were proven to be dominant in influencing passenger decisions. These findings underscore the need for route evaluation, fleet rejuvenation, and quality improvement so that public transportation services can once again function as an efficient, safe, and easily accessible mode of transportation for all levels of society.